Colours and maps for communicating natural hazards to users with and without colour vision deficiency. (15th June 2022) - Engeset, Rune Verpe; Pfuhl, Gerit; Orten, Camilla; Hendrikx, Jordy; Hetland, Audun
Abstract: Natural hazards are often communicated visually using colours and maps. However, users' ability to read and understand these products may be hampered by e.g., colour vision deficiency, potentially rendering the products less effective or even counter effective. To study these effects, we conducted two web-based surveys and analysed how to improve visual communication of avalanches, floods, landslides, and dangerous weather hazards. In survey 1 (n = 79), we tested four traffic light colour palettes, three map legends, and three map patterns used for communicating danger levels on the Norwegian website Varsom.no, to improve accessibility for individuals with and without colour vision deficiency (CVD). In survey 2 (n = 960), we tested four versions of traffic light colour palettes on a larger and international population. Survey 2 also tested six versions of Avalanche terrain exposure scale (ATES) maps on individuals with and without CVD varying in nationality, avalanche education and familiarity with ATES. Results suggest that the colours, legends, and maps used on Varsom should be improved, and that danger levels are best communicated with the colour palette used by Meteoalarm.info – in combination with symbols to help users with CVD. This study found that the colour scheme used for ski run difficulty in Europe was efficient for use with ATES maps for participants with and without CVD and is recommended as a worldwide standard for ATES. Further studies and testing of users' understanding are recommended to improve clarity of danger level maps and to improve visualization of ATES classes 0 and 1 on maps. Our studies show the hidden potential for efficient and inclusive communication of natural hazards and highlights the importance of including the needs of CVD users in standardisation efforts.